2021
DOI: 10.1088/2053-1591/abe6d5
|View full text |Cite
|
Sign up to set email alerts
|

Grain-refining of wire arc additive manufactured aluminum alloy with Nb powder addition

Abstract: Nb powder with an average diameter of 15 μm was added to the molten pool during wire arc additive manufacturing of 5B06 aluminum alloy. The unmelted Nb with high melting point and the in-situ alloying of Al3Nb acted as heterogeneous nucleation core. The fine equiaxed grains with a diameter less than 50 μm was achieved, and the texture intensity of which was obviously weakened. An improvement in both the ultimate tensile strength and elongation of the Nb added samples were observed, and the micro-hardness of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Since a lower gas flow rate leads to reduced convective cooling, the melt pool remains as a liquid for a longer period allowing trapped gas in the melt pool to escape, thus reducing porosity. Zhou et al [53] mixed Nb powder with a mean particle size of 15 μm to the molten pool during WAAM of 5B06 aluminium part. It was observed that fine equiaxed grains with a mean size of lesser than 50 μm were attained.…”
Section: D-printing Of Aluminium Components By Waammentioning
confidence: 99%
See 1 more Smart Citation
“…Since a lower gas flow rate leads to reduced convective cooling, the melt pool remains as a liquid for a longer period allowing trapped gas in the melt pool to escape, thus reducing porosity. Zhou et al [53] mixed Nb powder with a mean particle size of 15 μm to the molten pool during WAAM of 5B06 aluminium part. It was observed that fine equiaxed grains with a mean size of lesser than 50 μm were attained.…”
Section: D-printing Of Aluminium Components By Waammentioning
confidence: 99%
“…Table 4 To produce highly valued parts using WAAM technology, aluminium can be further alloyed with other alloying elements to improve its processabilities and mechanical performance [50]. As for the tensile strength, Table 4 reveals that some Al alloys like Al-Zn-Mg [55], Al3Nb [53], Al-Cu [35], Al-Mg-Mn [32], Al-Mg-Sc [67], Al-Mg-Si [12], Al 5183 [70] exhibited a high tensile strength of about 324, 360, 450, 344, 363, 354.5, and 293 MPa, respectively. As presented in Table 4, the yield strength of the selected WAAM Al alloys such as Al-Zn-Mg [55], Al-Mg-Mn [32], Al-Mg-Sc [67], Al-Cu [35], and Al-Mg-Si [12] indicated a high yield strength of 208, 240, 258, 305, 310 MPa respectively, while Al3Nb [53], Al 5183 [70], Al-Mg-Sc [67], Al-Mg [62], and Al 5356 [25] showed appreciable elongation of 20%, 20%, 26%, 27%, and 33%, respectively.…”
Section: D-printing Of Aluminium Components By Waammentioning
confidence: 99%
“…Niobium provides a similar effect as Ti in terms of grain refinement. The formation of the Al Nb phase significantly refined the WAAM microstructure of an Al-6Mg alloy [ 174 ]. A coarse columnar was changed to a fine equiaxed structure, which increased the ultimate tensile strength by 58 .…”
Section: Aluminum Alloys For Waammentioning
confidence: 99%
“…Zhou et al [11] on the other hand, added Nb particles with an average diameter of 15 µm mixed with ethanol to an 5000 aluminium alloy wire surface when temperature was higher than 150 ºC to ensure ethanol complete evaporation. The Nb reduced grain size signi cantly from 300 µm of grain diameter to less than 50 µm, and in addition, UTS higher than 360 MPa with an elongation of 20% was obtained for this alloy for the rst time.…”
Section: Introductionmentioning
confidence: 99%